Guidance note 2: selecting indicators for climate change adaptation programming - Bours, D; McGinn, C; Pringle, P (SEA Change CoP and UKCIP, 2014)
Climate change adaptation (CCA) programming is a complex, dynamic process that cuts across scales, sectors, and levels of intervention. CCA itself is characterised by many uncertainties, and it extends long past usual project cycles. Moreover, the evidence base of what works, where, and under what conditions is only beginning to emerge. How then to define, measure, and assess results of an adaptation programme? The complexities inherent in CCA pose a number of thorny challenges for evaluators; these were detailed in in Guidance Note 1 (Bours, McGinn, and Pringle 2014a). This second Guidance Note follows on from that discussion with a narrower question: how does one go about choosing appropriate indicators? We begin with a brief review of approaches to CCA programme design, monitoring, and evaluation (DME). We then go on to discuss how to identify appropriate indicators. We demonstrate that CCA does not necessarily call for a separate set of indicators; rather, the key is to select a medley that appropriately frames progress towards adaptation and resilience. To this end, we highlight the importance of process indicators, and conclude with remarks about how to use indicators thoughtfully and well.